2021
DOI: 10.3389/fimmu.2020.581911
|View full text |Cite
|
Sign up to set email alerts
|

The Cholinergic System Contributes to the Immunopathological Progression of Experimental Pulmonary Tuberculosis

Abstract: The cholinergic system is present in both bacteria and mammals and regulates inflammation during bacterial respiratory infections through neuronal and non-neuronal production of acetylcholine (ACh) and its receptors. However, the presence of this system during the immunopathogenesis of pulmonary tuberculosis (TB) in vivo and in its causative agent Mycobacterium tuberculosis (Mtb) has not been studied. Therefore, we used an experimental model of progressive pulmonary TB in BALB/c mice to quantify pulmonary ACh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 73 publications
(117 reference statements)
0
7
0
Order By: Relevance
“…The inflammatory response of bronchial epithelial cells is a critical pathogenic mechanism of airway homeostasis and pulmonary diseases [ 1 , 3 , 4 ]. Considering the complications of airway inflammation, the emergence of novel targets might improve further understanding and treatment of chronic inflammation in the respiratory tract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inflammatory response of bronchial epithelial cells is a critical pathogenic mechanism of airway homeostasis and pulmonary diseases [ 1 , 3 , 4 ]. Considering the complications of airway inflammation, the emergence of novel targets might improve further understanding and treatment of chronic inflammation in the respiratory tract.…”
Section: Discussionmentioning
confidence: 99%
“…The bronchial epithelium is the first anatomical barrier for stimulus and pathogens. Once a stimulus activates bronchial epithelial cells, a series of inflammatory cascades are initiated, accompanied by excessive release of inflammatory cytokines, which eventually lead to cell apoptosis [ 3 , 4 ]. To better understand this complex process, it is important to elucidate the regulatory mechanisms and identify more effective targets of inflammatory response in bronchial epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, nicotine has the potential to increase the growth of Mtb mainly in type II pneumocytes, and inhibit the expression of antimicrobial peptides in type II pneumocytes and airway basal epithelial cells partially mediated by the α7nAChR [ 134 ]. During the periods of experimental pulmonary tuberculosis, there are high concentrations of ACh and expression of choline acetyltransferase (ChAT) in lung epithelial cells and macrophages at the early infection stage, besides, the upregulation of lung ACh was even higher and coincided with ChAT and α7nAChR subunit expression in immune cells at late progressive TB [ 135 ]. Surprisingly, in vitro studies revealed that the bacteria have the potential to produce nanomolar concentrations of ACh in liquid culture and the administration of ACh/nicotinic antagonists to Mtb cultures can promote or inhibit bacterial proliferation, respectively.…”
Section: Acetylcholine System In Tuberculosismentioning
confidence: 99%
“…It is unclear how acetylcholine results in the suppression of Mtb clearance. Given the recent findings that acetylcholine and cholinergic system favor the progression of mycobacterial infection (70), targeting the non-neuronal cholinergic system in the lungs may contribute to the development of new therapeutics against TB.…”
Section: Role Of Arg Metabolism During Mycobacterial Infectionmentioning
confidence: 99%